Risky Sexual Behavior Among Foster Care Adolescents: A Social Cognitive Theory Perspective - Hariadi, Febri; Puspita, Alda Tiara; Daud, Muhammad Muzhaffar; Fieldhathama, Fedhilla; Kusumawati, Aditya (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Previous studies have shown that 3.6% of male adolescents in Indonesia have engaged in sexual intercourse, with permissive neglectful parenting identified as a significant contributing factor. Many children in Indonesia grow up without adequate parental care, leading to the establishment of nonprofit social organizations such as SOS Children's Village Semarang. This study aims to identify the factors contributing to risky sexual behavior among foster care adolescents at SOS Children's Village Semarang using the framework of social cognitive theory.Method: This study employed a mixed-methods approach with a sequential explanatory design. Quantitative data were collected through questionnaires, followed by qualitative data collection through observations and in-depth interviews. Binary logistic regression was used to analyze the quantitative data, while content analysis was used to analyze the qualitative data.Result: This study found that personal factors, including knowledge, attitudes, and expectations, along with environmental factors such as social norms and peer group influence, significantly contribute to risky sexual behavior among foster care adolescents. These findings emphasize the need for comprehensive interventions involving foster parents, orphanage staff, and peers to improve adolescents' understanding of sexual risks, promote positive attitudes toward sexuality, and strengthen their ability to resist negative peer pressures.